"To the End of the Line": The Romanian Army in Operation Barbarossa. Issue 4 (2nd October 2021) - Harward, Grant T.
ABSTRACT: This article uses the 80th anniversary of Nazi Germany's invasion of the Soviet Union to re-examine Romania's role in Operation Barbarossa . Its primary aim is to refute the myth that Romanian soldiers lacked motivation and support for the war, which supposedly quickly eroded after the Romanian Army reconquered territory occupied by the USSR a year prior. The conventional view arguing in favor of Romania being a reluctant Axis ally points to the fact that after initially fielding two armies in June 1941, it only had a corps on the front line in December 1941. This article argues that this was actually the result of German skepticism — based on legitimate professional criticism and bogus racist theories — of the combat value of Romanian soldiers and German logistical inability to supply its own forces, much less those of its allies, as the campaign dragged on. The author argues that Romanian soldiers were actually highly motivated by ideology to fight against the alleged threat of 'Judeo-Bolshevism'. Although the Romanian Army did suffer many weaknesses in training, equipment, and leadership, it could rely on officers and enlisted men willing to fight with determination against the Red Army and commit atrocities against Jews. This article shows both sides of Romania's 'holy war' by combining military and Holocaust perspectives as both fighting and mass murder were closely related on the Eastern Front. This wider perspective also highlights the importance of several more Romanian corps helping to occupy parts of Ukraine in the rear to allow German troops to be spared for operations on the front as Nazi Germany tried to win final victory before Christmas. Romania's holy war complemented Nazi Germany's race war and bound the two tightly together on the Eastern Front even after Operation Barbarossa failed to destroy the Soviet Union.